Answer: q = -2/3
Step-by-step explanation: To find q, we first need to remove the parentheses on the left side of the equation. We can do this by multiplying everything outside the parentheses by everything inside them.
3 (q + 4/3) = 2
3q + 3 · 4/3 = 2
3q + 4 = 2
Now, we need to move the 4 to the other side of the equal sign. To do this, we just need to change its sign when moving it:
3q = 2 - 4
3q = -2
All we have to do next is divide both sides of the equation by 3 so we can fully isolate the q:
3q/3 = -2/3
q = -2/3